THE DEVELOPMENT OF WORKSHEET BASED ON PROBLEM BASED LEARNING – THINKING MAPS STRATEGY TO INCREASE THE CRITICAL THINKING OF PRIMARY STUDENTS - Ambarita, Alben; Dewi, Ratna; Caswita; Surbakti, Arwin; Wahyudi, Apri (International Journal of Psychosocial Rehabilitation, 2020)
The goal of this experiment and development is to enhance worksheet which is on the basic of problem based learning with the strategy of thinking maps in proper way and increase the skill of critical thinking effectively. This method of observation uses the Borg and Gall’s design. The populations of this experiment are the fifth grades students from Lampung Tengah Primary School in Lampung Province, Indonesia worksheet product validated media expert, theory expert and practitioner. Data collector uses a valid and reliable objective test instrument. Data analysis operates N-Gain. The research result showed that worksheet is valid and decent to be used and it’s very convincing to expanse students critical mind skill.